The Potential of Tumor Debulking to Support Molecular Targeted Therapies - Oppel, Felix; Görner, Martin; Sudhoff, Holger (Frontiers in Oncology, 2020)
Tumors may consist of billions of cells which in malignant cases disseminate and form distant metastases. The large number of tumor cells formed by the high number of cell divisions during carcinogenesis and tumor progression creates a heterogeneous set of genetically diverse tumor cell clones by statistical means. For cancer therapy this implicates high challenges, as distinct clones have to be targeted in distinct tissue locations. Recent research has led to the development of specific inhibitors of defined target effectors in cellular signaling cascades which promise more effective and more tumor-specific therapy approaches. Many of these molecular targeted therapy (MTT) compounds have already been translated into clinics or are currently being tested in clinical studies. However, the outgrowth of tumor cell clones resistant towards such inhibitors is a drawback that affects specific inhibitors the same way as classical cytotoxic chemotherapeutics, because additionally acquired genetic alterations can enable tumor cells to circumvent particular regulators of cellular signaling being targeted. Thus, it might be desirable to reduce genetic heterogeneity prior of molecular targeting which could reduce the statistical chance of tumor relapse initiated by resistant clones. One way to achieve that are unspecific methods to remove as much tumor material as possible before applying MTT, e.g. tumor bebulking. Currently, this is successfully applied in clinical treatment of ovarian cancer. We believe that tumor debulking followed by treatment with a combination of molecular targeted drugs, optimally guided by biomarkers, might advance survival of patients with various cancer types.